Assessment of Risk and Uncertainties Among Poultry Farmers in Corcuera, Romblon - Falculan, Ken N. (Indonesian Journal of Agriculture and Environmental Analytics, 2023)
Poultry farming is known widely all over the country, especially since it is considered a source of income for Filipino farmers. This study used a descriptive method to assess the practices of poultry farmers in eliminating risks. Most of the respondents agreed on the different risks in managing poultry this is the following; environmental risks, production risks, health risks, market risks, and financial risks. Determinants are; disease outbreaks, poultry facilities, veterinary care, supply of electricity and water, inadequate knowledge of poultry raising, and high feed prices. Most respondents stated that; management and strategic intervention will be applied in managing small-scale poultry. Such interventions stated are; promoting the quality of poultry products, maintaining poultry health and sanitation, having strong communication and coordination between all those involved in poultry veterinary service, having personal savings, investing in quality feeds, and biosecurity obtained.